Audience effects in sooty mangabey agonistic behavior - Quintero, Fredy; Touitou, Sonia; Magris, Martina; Zuberbühler, Klaus (Frontiers in Psychology, 2025)
The term ‘Audience Effects’, refers to behavioral changes triggered by the mere presence of others and has been extensively studied in animals to explore their capacity for social awareness and intentionality. Research shows that a wide range of species—from insects to primates—alter behaviors depending on their audience, with primates, especially great apes, demonstrating the most complex audience-aware behaviors, such as adjusting communication based on the recipient’s attention or understanding. These findings suggest that some animals can infer intentions, remember social dynamics, and strategically act depending on who is watching. However, there is still limited data from non-ape primates and other mammals, raising questions about whether such cognitive traits evolved through shared ancestry or convergent evolution. Aggressive behaviors also reveal audience effects, with individuals, especially lower-ranking ones, using strategic aggression in front of influential bystanders to influence future interactions. In this study, we used focal animal sampling to investigate how free-ranging sooty mangabeys, a terrestrial forest-dwelling primate living in large groups, used aggression depending on the composition of the audience. We found that individuals were significantly more aggressive to opponents if they were observed by large audiences that contained higher ranking individuals. These displays of aggression were often accompanied by vocalizations, further suggesting that aggressors were interested in attracting the audience’s attention. We discuss these patterns of audience-dependent aggressive behavior and propose that sooty mangabeys adjust their social behavior depending on the composition of the bystanding audience, reacting in the most appropriate way depending on the situation, which provides additional support to the growing body of research showing that the underlying mechanisms necessary for the evolution of complex social cognition are more widespread in the animal kingdom than was previously thought.